PENGARUH PENAMBAHAN JUMLAH INOKULUM DAN DI-KALIUM HIDROGEN FOSFAT PADA FERMENTASI PRODUKSI DEKSTRAN - Triantarti, Triantarti; M, Hendro Santoso (Research Center for Biology-Indonesian Institute of Sciences, 2004)
Dextran production is conducted by fermentation by using Leuconostoc mesenteriodes wich produces dextransucrase enzyme.Sucrose is converted to dextran by dextransucrase. Sucrose is a main carbon source in dextran fermentation. Hence, sugar cane juice mainly contains sucrose is potential material for dextran fermentation. The effect of inoculum concentration added at the beginning of fermentation of di-potassium hydrogen phosphate concentration in the medium were studied. L.mesenteroides B-512F was used. The results showed that there were no effect on optimum growth and dextran production when the inoculum concentration added at 1% and 5%(w/v). The only difference was inoculum at 1% (w/v) delaying the growth and dextran formation in comparison to the addition of 5%(w/v) inoculum. The optimum growth and dextran production were affected by di-potassium hydrogen phosphate concentration in the medium (0,5, 1,0 and 1,5% w/v).The growth was highest at di-potassium hydrogen phosphate concentration 1,5 % w/v. On the otherhand, dextran production was lower compared to the other treatments.